La Nana (2009): una sociología de los medicamentos y su relación con el trabajo en Chile. - Millones Espinosa, Mario (Journal of Medicine & Movies / Revista de Medicina y Cine, 2016)
The aim of this article is presente a problem from the sociology around health and work relationship. Through the film The maid (2009), i said as hypothesis that the use of analgesic medicine at work has a dual function arises: first, individualize the problema of working conditions and, second, transforms into a body only problem. In other words, the analgesic medicine in the present allows the bodies to continue working under a logic of yield and working problematic conditions are hidden under the individualization of health.